2019
DOI: 10.1042/bsr20182278
|View full text |Cite
|
Sign up to set email alerts
|

Association between epicardial adipose tissue and adverse outcomes in coronary heart disease patients with percutaneous coronary intervention

Abstract: We assessed the relationship between the volume of epicardial adipose tissue and long-term outcomes in patients with coronary heart disease (CHD) undergoing percutaneous coronary intervention (PCI). The patients with CHD were followed for at least 2 years after PCI. The epicardial adipose tissue volume (EATV) was measured using multi-slice computed tomography. Cox regression analysis was used to examine the relationship between EATV and clinical outcome. In this study, 500 patients were enrolled and followed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 34 publications
1
12
0
1
Order By: Relevance
“…The other 4 studies solely showed the relationship between EAT and ISR of patients treated with PCI [9][10][11][12]. The impact of EAT on MACEs for patients treated PCI was evaluated in other 2 studies [4,5]. Two studies lonely measured the in uence of EAT on no-re ow of patients with STEMI treated with primary PCI [15,17].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The other 4 studies solely showed the relationship between EAT and ISR of patients treated with PCI [9][10][11][12]. The impact of EAT on MACEs for patients treated PCI was evaluated in other 2 studies [4,5]. Two studies lonely measured the in uence of EAT on no-re ow of patients with STEMI treated with primary PCI [15,17].…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating evidences suggest that the prognostic value of epicardial adipose tissue (EAT) on no-re ow, ISR, infarct size and MACE for the patients treated with PCI [4,5]. previous meta-analysis has been demonstrated that elevated location-speci c EAT thickness at the left atrioventricular groove is associated with obstructive coronary artery disease [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Epicardial fat is visceral thoracic fat and known to be related to the presence of dyslipidemia and coronary arterial stenosis in the patients after PCI [14]. Epicardial adipose tissue volume (EATV) is an independent indicator of long-term main adverse cardiovascular events in CHD patients after PCI [15] and affected by adipose tissue dysfunction. HR variability is also influenced by epicardial fat [16].…”
Section: Introductionmentioning
confidence: 99%